International cooperation and development: a conceptual overview - Sebastian Paulo (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Any credible claim to implement an agenda for global development – such as currently discussed in the post-2015 process – will require integrating the broader framework of international cooperation into this effort. A wide, but vague consensus that global framework conditions matter for development has already existed in past development debates. However, good resolutions such as MDG 8 for a global partnership have shown insufficient progress in practice. This paper reviews key aspects of the relationship between international cooperation and development at a conceptual level. Drawing on a distinction between domestic and global public goods as enablers and goals of development, the paper first illustrates the role of international cooperation and its interdependence with domestic action. The framework identifies contact points in the relationship between global and domestic action and goals with the categories of provision, support, access and preservation. The second part of the paper reviews key concepts of patterns of international cooperation that represent the elements of the global governance framework to which a broadening development agenda needs to link up more strongly. Overall, the conceptual review underlines that the question of how international cooperation works has moved to the centre of development studies. Yet, an even bigger challenge than achieving cooperation in the first place might be to steer the complex architecture and processes of international cooperation towards contributing to a global agenda for development.
Keywords: 330; Regionale + globale + transnationale Governance